2010
DOI: 10.1111/j.1462-2920.2009.02119.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genomic diversity of Lactobacillus plantarum strains isolated from various environmental niches

Abstract: Lactobacillus plantarum is a ubiquitous microorganism that is able to colonize several ecological niches, including vegetables, meat, dairy substrates and the gastro-intestinal tract. An extensive phenotypic and genomic diversity analysis was conducted to elucidate the molecular basis of the high flexibility and versatility of this species. First, 185 isolates from diverse environments were phenotypically characterized by evaluating their fermentation and growth characteristics. Strains clustered largely toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
293
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 276 publications
(316 citation statements)
references
References 52 publications
(137 reference statements)
21
293
2
Order By: Relevance
“…argentoratensis, for analysis of whole-cell extracts by SDS-PAGE and GlcNAc-specific sWGA blotting. Notably, these 9 strains were selected to maximize the coverage of the phylogenetic tree based on the whole-genome comparative genome hybridization data sets (56), as well as to include strains isolated from diverse niches ( Table 1). All selected strains, including NCIMB12120, displayed sWGA-recognized glycosylated proteins that showed similar banding patterns on SDS-PAGE gels (Fig.…”
Section: Protein O-glycosylation In Lactobacillus Plantarummentioning
confidence: 99%
“…argentoratensis, for analysis of whole-cell extracts by SDS-PAGE and GlcNAc-specific sWGA blotting. Notably, these 9 strains were selected to maximize the coverage of the phylogenetic tree based on the whole-genome comparative genome hybridization data sets (56), as well as to include strains isolated from diverse niches ( Table 1). All selected strains, including NCIMB12120, displayed sWGA-recognized glycosylated proteins that showed similar banding patterns on SDS-PAGE gels (Fig.…”
Section: Protein O-glycosylation In Lactobacillus Plantarummentioning
confidence: 99%
“…The strain variability observed in L. plantarum might be related to the high genetic diversity reported for this species (Sanders et al, 2015;Siezen et al, 2010;Siezen and van Hylckama Vlieg, 2011), which corresponded to the observed phenotypic diversity, including the strain diversity in stress tolerance. A clear example for the observed strain variability in growth kinetics is given for strain FBR26.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the strain variability is obtained by taking measurement using different strains from the same species or more widely known as between strain variability. Although belonging to one species, each strain might show different genotypic and phenotypic characteristics (De Jesús and Whiting, 2003;Donaldson et al, 2009;Nelson et al, 2004;Sanders et al, 2015;Siezen et al, 2010;Siezen and van Hylckama Vlieg, 2011;Whiting and Golden, 2002). Since one species consists of a wide range of strains, one might expect that strain variability is higher than reproduction variability and experimental error.…”
Section: Variation: Variability and Uncertaintymentioning
confidence: 99%
See 2 more Smart Citations